Analisis Corporate Governance dan Firm Characteristics terhadap Sustainability Reporting BUS di Indonesia - Silvia Utami Ningtias; Purbayati, Radia; Laksana, Banter (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The idea behind this research is the uneven implementation of sustainability reporting in Sharia Commercial Banks in Indonesia since the publication of regulation Number 51/POJK.03/2017. This research intends to inspect the influence of corporate governance as proxied by the board of directors and independent board of commissioners and firm characteristics as proxied by ROA and company age on sustainability reporting (SR) as proxied by GRI-G4. This study employed a quantitative explanatory methodology. Results from the research show that company age has a substantial and unidirectional impact on SR. The result also showed a considerable effect in contradictory directions between the independent board of commissioners and SR. Meanwhile, ROA and the board of directors do not impact SR. However, simultaneously, the board of directors, independent board of commissioners, ROA, and company age have a significant and unidirectional impact on SR.